Asa and the Little Stream - Adimora-Ezeigbo, Akachi (Literamed Publications, 2004)
A magician visits Lubelu land and informs Chief Igunu of a river that possesses curative powers. His daughter, Princess Akudu loves adventure and decides to go on a spree with Asa, her slave. The two girls and some grown-up palace attendants embark on the journey to the beautiful River. They encounter series of hitches on the way but Asa was fortunate to come in contact with Prince Eras of Falala land who later takes her to his town and gets married to her.
Keywords: Adventure; Fairytales; Tales